PENYIARAN FILM TANPA SENSOR DI PLATFORM NETFLIX - Ajeng Septianur Putri; Kristoforus Laga Kleden (Gapenas Publisher, 2022)
The development of technology and information has implications for the broadcasting industry which has changed almost every aspect of human life. Broadcasting which was originally only through conventional media, namely radio frequency spectrum over the air and cable such as television or radio, is now starting to shift to digital broadcasting media using digital platforms which can be accessed via an internet connection. This type of research is normative legal in nature and is conducted in order to address legal issues. Utilizing research methods that incorporate both a statutory and conceptual approach. Netflix broadcasts film content that contains elements of violence and pornography. This of course violates the existing laws and regulations in Indonesia. If KPI oversees broadcast content on the Netflix platform, then this is outside of its duties and authorities and is not in accordance with the concept of broadcasting based on the Broadcasting Law. Good law is dynamic law that develops according to the times and the dynamics of society. The Broadcasting Law must be amended immediately because it is no longer relevant to the current broadcasting technology. In terms of expanding the authority of KPI to supervise broadcast content in digital media, this is outside the duties and authorities of KPI and is not in accordance with the concept of broadcasting based on the Broadcasting Law